Endovascular Treatment of Splanchnic Pseudoaneurysms Following Blunt Solid Organ Injuries in Children - Oliveira, João André (2018)
Non operative management is currently the standard treatment of blunt abdominal solid organ injuries grades I-IV (American Association for the Surgery of Trauma’s organ injury scale) in children. Even though post-traumatic splanchnic pseudoaneurysms are an infrequent complication, they may potentially lead to life-threatening intra-peritoneal or retroperitoneal bleeding. In adults, the relationship between failure of conservative management in abdominal trauma patients and delayed rupture of a pseudoaneurysm identified in follow-up imaging is well established, as is the capability of selective angioembolization to decrease non operative management failure rate. In the pediatric population, the clinical and prognostic significance of splanchnic pseudoaneurysms remains controversial and, currently, there are no high-level evidence-based guidelines on its management. The authors of this paper present 3 cases of post-traumatic abdominal pseudoaneurysms in children which were identified in imaging exams after conservative management, successfully treated by selective embolization, and a review of the literature regarding this subject is also presented. Although prospective randomized-controlled trials are needed to better define the incidence, natural history and optimal management of abdominal PAs in pediatric blunt abdominal trauma, we believe that selective angioembolization provides a safe and effective therapy for its treatment and should be considered as part of the multidisciplinary trauma management protocol in children.